PENGEMBANGAN INSTRUMEN MENGGUNAKAN SPINNER QUESTION UNTUK MEMFASILITASI MINAT BELAJAR PESERTA DIDIK SMP PADA MATERI TATA SURYA - Labibah, Hana; Vitasari, Mudmainah; Rohimah, Ratu Bai (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Students' interest in learning is one of the important factors in the success of science learning, especially in the Solar System material which is abstract and requires active student involvement. However, the instruments used in schools are generally still conventional, so they are less capable of facilitating students' interest in learning. This study aims to develop and test the feasibility of the Spinner Question instrument in facilitating middle school students' interest in learning about the Solar System. This study uses a research method called Research and Development (R&D) with the Borg and Gall model modified into six stages, namely research and information collection, planning, developing a preliminary form of the product, preliminary field testing, main product revision, and main field testing. The research subjects involved seventh-grade students at SMP Negeri 1 Ciomas, as well as validation by content experts, media experts, instrument experts, and practitioners. The developed instrument consisted of a test instrument containing essay questions. Instrument validation was conducted theoretically through assessments by content experts, media experts, instrument experts, and practitioners, as well as empirically through item analysis including validity test, reliability, difficulty level, and discriminating power. The results of the study showed that the instrument using Spinner Question obtained a validity percentage of 90.35%, categorized as